Development of Clothing Information System base Android Applications of Boutique Modiste Shofi Samarinda - Kurnia; Yulianto; Budi Rachmadani (TEPIAN, 2022)
Development of Apparel Information System Applications at Fashion Boutique Shofi Samarinda Based on Android. Modiste Shofi Boutique is one of the boutiques that provide various types of men's and women's clothing for sales such as batik clothes, negligees, party dresses, masks, mokena, and others. The promotion and marketing carried out by the Modiste Shofi Boutique are inadequate so that there are still many people who do not know the existence of the Modiste Shofi Boutique. In addition, sales at the Modiste Shofi Boutique are only conventional where customers have to come directly to the Boutique to buy clothes. The results of this study are to create an application for selling clothes at the Modiste Shofi Boutique in order to promote clothes that are sold widely and make it easier for customers to make purchases without coming directly to the Modiste Shofi Boutique. Based on testing using the UML (Unified Modeling Language) method which consists of testing application analysis and implementation, it can be said that the Development of the Clothing Information System Application at the Android-Based Modiste Shofi Boutique can run smoothly and represent the features contained in the Android Application. Test results on users show that the application of ordering clothes has an adequate appearance (user friendly), the structure of the application is easy to learn, the commands or instructions are easy to use, the time used to process data is relatively fast and the resulting information is accurate.